Feasibility of quantum key distribution with macroscopically bright coherent light - Kovalenko, Olena; Spasibko, Kirill; Chekhova, Maria; Usenko, Vladyslav C.; Filip, Radim (Optics Express, 2019)
We address feasibility of continuous-variable quantum key distribution using bright multimode coherent states of light and homodyne detection. We experimentally verify the possibility to properly select signal modes by matching them with the local oscillator and this way to decrease the quadrature noise concerned with unmatched bright modes. We apply the results to theoretically predict the performance of continuous-variable quantum key distribution scheme using multimode coherent states in scenarios where modulation is applied either to all the modes or only to the matched ones, and confirm that the protocol is feasible at high overall brightness. Our results open the pathway towards full-scale implementation of quantum key distribution using bright light, thus bringing quantum communication closer to classical optics.
CRIS-Team Scopus Importer:2019-12-24

Optical harmonic generation from bright squeezed vacuum - Spasibko, Kirill; Kopylov, Denis A.; Krutyanskiy, Victor L.; Murzina, Tatiana V.; Leuchs, Gerd; Chekhova, Maria (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27